The Practice of Neoliberal Multiculturalism in Urban Management in British Cities: a Case Study from London’s Chinatown - Quoc-Dung Dang (Cahiers du MIMMOC)
This research paper delves into the practice of neoliberal multiculturalism in the urban management of London’s Chinatown, serving as a case study to elucidate broader urban dynamics. It examines the intersection of public-private partnerships and multicultural policies within a neoliberal framework, exploring how these elements coalesce to shape Chinatown’s development. The analysis highlights how cultural elements are utilised within market-driven agendas, reflecting on the strategic use of Chinatown's cultural identity to enhance its marketability and economic value in the global urban landscape.